Cerebrospinal Fluid IL-6, TNF-α and MCP-1 in Children with Acute Lymphoblastic Leukaemia during Chemotherapy - Protas, P. T.; Holownia, A.; Muszynska-Roslan, K.; Wielgat, P.; Krawczuk-Rybak, M.; Braszko, J. J. (Neuropediatrics, 2011)
The aim of the study was to investigate the levels of cerebrospinal fluid (CSF) cytokines during chemotherapy of acute lymphoblastic leukaemia (ALL). Examination of 12 ALL child (6 boys and 6 girls) patients evidenced significant increases in interleukin-6 (IL-6) and monocyte chemotactic protein-1 (MCP-1) after induction treatment and significant increases in IL-6, tumour necrosis factor-α (TNF-α) and MCP-1 levels during the consolidation phase, as compared to their values at the time of diagnosis. There were no significant differences in CSF IL-6, TNF-α and MCP-1 concentrations after therapy. Our data suggest that standard ALL treatment may cause a subclinical inflammation and neurotoxicity.
Keywords: acute lymphoblastic leukaemia; chemotherapy; IL-6; MCP-1; neurotoxicity; TNF-α